Treatment tapering and stopping in patients with rheumatoid arthritis in stable remission (RETRO): a multicentre, randomised, controlled, open-label, phase 3 trial. (November 2021) - Tascilar, Koray; Hagen, Melanie; Kleyer, Arnd; Simon, David; Reiser, Michaela; Hueber, Axel J; Manger, Bernhard; Englbrecht, Matthias; Finzel, Stephanie; Tony, Hans-Peter; Schuch, Florian; Kleinert, Stefan; et al.
Summary: Background: Owing to increasing remission rates, the management of patients with rheumatoid arthritis in sustained remission is of growing interest. The Rheumatoid Arthritis in Ongoing Remission (RETRO) study investigated tapering and withdrawal of disease-modifying antirheumatic drugs (DMARDs) in patients with rheumatoid arthritis in stable remission to test whether remission could be retained without the need to take DMARD therapy despite an absence of symptoms. Methods: RETRO was an investigator-initiated, multicentre, prospective, randomised, controlled, open-label, parallel-group phase 3 trial in patients aged at least 18 years with rheumatoid arthritis for at least 12 months before randomisation who were in sustained Disease Activity Score using 28 joints with erythrocyte sedimentation rate (ESR) remission (score <2·6 units). Eligible patients were recruited consecutively from 14 German hospitals or rheumatology practices and randomly assigned (1:1:1) without stratification and regardless of baseline treatment, using a sequence that was computer-generated by the study statistician, to continue 100% dose DMARD (continue group), taper to 50% dose DMARD (taper group), or 50% dose DMARD for 6 months before stopping DMARDs (stop group). Neither patients nor investigators were masked to the treatment assignment. Patients were assessed every 3 months and screened for disease activity and relapse. The primary endpoint was the proportion of patients in sustained DAS28-ESR remission without relapse at 12 months, analysed using a log-rank test of trend and Cox regression. Analysis by a trained statistician of the primary outcome and safety was done in a modified intention-to-treat population that included participants with non-missing baseline data. This study is completed and closed to new participants and is registered with ClinicalTrials.gov (NCT02779114 ). Findings: Between May 26, 2010, and May 29, 2018, 303 patients were enrolled and allocated to continue (n=100), taper (n=102), or stop DMARDs (n=101). 282 (93%) of 303 patients were analysed (93 [93%] of 100 for continue, 93 [91%] of 102 for taper, and 96 [95%] of 101 for stop). Remission was maintained at 12 months by 81·2% (95% CI 73·3–90·0) in the continue group, 58·6% (49·2–70·0) in the taper group, and 43·3% (34·6–55·5) in the stop group (p=0·0005 with log-rank test for trend). Hazard ratios for relapse were 3·02 (1·69–5·40; p=0.0003) for the taper group and 4·34 (2·48–7·60; p<0.0001)) for the stop group, in comparison with the continue group. The majority of patients who relapsed regained remission after reintroduction of 100% dose DMARDs. Serious adverse events occurred in ten of 93 (11%) patients in the continue group, seven of 93 (8%) patients in taper group, and 13 of 96 (14%) patients in the stop group. None were considered to be related to the intervention. The most frequent type of serious adverse event was injuries or procedural complications (n=9). Interpretation: Reducing antirheumatic drugs in patients with rheumatoid arthritis in stable remission is feasible, with maintenance of remission occurring in about half of the patients. Because relapse rates were significantly higher in patients who tapered or stopped antirheumatic drugs than in patients who continued with a 100% dose, such approaches will require tight monitoring of disease activity. However, remission was regained after reintroduction of antirheumatic treatments in most of those who relapsed in this study. These results might help to prevent overtreatment in a substantial number of patients with rheumatoid arthritis. Funding: None.